Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In Abstract and Concrete Category of Adamek, Herrlich and Stretcker, I'm dealing with exercise 7Dd. It says that a strict monomorphism $f:A\to B$ followed by a section $g:B\to C$ give rise to a a strict monomorphism $fg:A\to C$.

I try to prove it: Let $f'$ such that, for any $r,s:C\to\cdot$,we have $fgr=fgs$ implies $f'r=f's$. We have to show that $f'=af$ for a unique $a$. Let $h$ such that $gh=1$. Then $fu=fv$ implies $fghu=fghv$ which implies $f'hu=f'hv$. Since $f'$ is strict, by assumption, we obtain $f'h=af$ for a unique $f$. I have difficulties to deduce $f'=afg$ from it.

share|cite|improve this question
up vote 0 down vote accepted

Let $E$ denote the domain of $f'$. The trick is to factor $f': E \to C$ through $g$ first, using the fact that $g$ is the equalizer of the pair $hg, 1_C: C \to C$. Indeed, since $fg(hg) = fg(1_C)$, we have $f'(hg) = f' 1_C$ by hypothesis. Because of the observation of $g$ being the equalizer, we can therefore write $f' = bg$ for some (unique) $b: E \to B$.

Again by hypothesis, we have that $f' = bg$ equalizes every pair $r, s: C \to D$ that is equalized by $fg$, i.e.,

$$fgr = fgs \Rightarrow bgr = bgs.$$

In particular, using $gh = 1_B$, we now have a sequence of implications

$$fr' = fs' \Rightarrow fg(hr') = fg(hs') \Rightarrow bg(hr') = bg(hs') \Rightarrow br' = bs'$$

so that by strictness of $f$, we may write $b = af$ for some (unique) $a$. We conclude $f' = bg = afg$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.